Utilization of the Kinemaster Application as a Science Learning Media - Ferdinand Salomo Leuwol; Andi Asrijal; Usmaedi Usmaedi; Anto Susanto (P3M IAI Nusantara Batang Hari, 2024)
To foster the spirit of learning in 5th graders at SD 22 Baringin towards science subjects (Natural Sciences), educators are expected to be able to create a media, so that teaching and learning activities are easy to understand, interesting, and easily absorbed by students. Especially now, various countries including Indonesia are being hit by COVID-19. Of course, this has forced the government, as well as schools, to stop all activities in order to stop the spread of COVID-19. This epidemic is certainly very influential on education, where teaching and learning activities that were originally carried out face-to-face, are now turning into online learning (in the network), namely learning without face-to-face, which is carried out from home. With these circumstances, of course, make students and teachers have difficulty in teaching and learning activities. Therefore, educators are asked to be creative in designing all things related to learning activities, namely by making a good media in the form of videos, posters, animated images and others. To create interesting learning media, educators can take advantage of the kinemaster application. This application can provide convenience for all of us in video editing, especially for educators. Kinemaster is an application that provides a complete range of features and effects, this application is also free and easily accessible to many people, no wonder many people use this application to make interesting learning videos.